Preferred Institutions: Public Views on Policy - (:unkn) unknown (My University, 2017)
In this dissertation, I ask why people might prefer one institution of government (courts, legislatures, executives) over another to handle certain issues. Previous research has focused on legitimacy of the courts, whether institutions can legitimate policy, and how public opinion is thus informed. This research is invaluable in understanding support for and influence of specific institutions, but this only gets us so far. We still do not know why people might feel that one institution is more legitimate than another to handle policymaking on a specific issue. Here, I begin to examine this question arguing that institutions act as source cues to individuals and that those individuals evaluate the appropriateness of institutions to handle issues by considering institutional design (majoritarianism v. countermajoritarianism), politics (political v. nonpolitical institutions and issues), trust, and regret/disappointment. In short, I suggest that numerous factors play into an individual’s preferences for one branch to handle certain issues and that these factors have to do both with beliefs about the institution(s), and perceptions of the issue(s).
Keywords: Institutions; Legitimacy; Policy Acceptance; Preference; Public Opinion